Side Effects of Methotrexate for Psoriasis Therapy - Melida Agustina; Afif Nurul Hidayati; Nurina Hasanatuludhhiyah (Department of Dermatology and Venereology, Faculty of Medicine, Universitas Airlangga, 2020)
Background: Psoriasis is a chronic and relapsing inflammatory disease of the skin, characterized by the presence of well-defined erythematous plaque covered by silvery-white scales. Methotrexate is a folic acid antimetabolic for psoriasis therapy and given systemically so unexpected effects can occur. Purpose: To evaluate the side effects of methotrexate as therapy in psoriasis. Methods: The descriptive research based on the medical record of psoriasis patients who were treated for hospitalization on at Kemuning I and II ward Dr. Soetomo General Academic Hospital Surabaya during the period January 2017 - December 2018. The sampling method used was total sampling. Result: Twenty two psoriasis patients receiving methotrexate therapy with the dose of methotrexate is 10-15 mg once weekly, there were 4.5% low erythrocyte level, 27.3% high leukocyte level, 13.6% high thrombocyte level, 18.2% high SGOT level, 22.8% high SGPT level, 18% nausea, 9.1% vomiting, 4.6% headache, and 4.6% shortness of breath. Conclusion: Methotrexate for psoriasis therapy may cause several side effects even not the severe ones, therefore careful dosing and side effect monitoring are necessary.